(untitled) (Academia Journal of Medicine, 2026)
Oral submucous fibrosis (OSMF) is a chronic, progressive, potentially malignant disorder predominantly associated with areca nut consumption. It is characterized by fibrosis of the oral mucosa, leading to restricted mouth opening and increased risk of malignant transformation into oral squamous cell carcinoma (OSCC). The rate of malignant transformation varies widely, emphasizing the need for early identification of high-risk individuals. This review aims to summarize the key risk factors and emerging biomarkers associated with malignant transformation in OSMF. Major risk factors include prolonged areca nut use, tobacco consumption, genetic susceptibility, nutritional deficiencies, and chronic inflammation. Recent advances have highlighted the role of molecular biomarkers such as p53, Ki-67, cyclin D1, and various salivary and serum markers in predicting malignant potential. Understanding these factors is crucial for early diagnosis, risk stratification, and timely intervention. The integration of clinical assessment with molecular diagnostics may improve patient outcomes and reduce the burden of oral cancer.